Waste-wood derived biochar as a support for horseradish peroxidase immobilization - Petronijević Mirjana; Panić Sanja; Đurović-Mladenović Nataša; Savić Saša; International Symposium on Analytical and Environmental Problems (26.) (2020) (Szeged) (2020)
In this paper, the suitability of waste-wood derived biochar particles as a support for the horseradish peroxidase (HRP) immobilization by adsorption method was investigated. The change in enzymatic activity of the immobilized enzyme at different values of pH and temperature, as well as stability over time, was measured. The results showed that HRP can efficiently bind to biochar particles by adsorption. The immobilized enzyme shows high activity (>80%) at a wide range of pH (7-9) and temperature (20-50°C). The immobilized enzyme retains 22% and 40% of its activity during storage at temperatures of 25 and 10°C after a period of 30 days, respectively.
Keywords: Természettudományok; Kémiai tudományok